A Long Noncoding Way to Alternative Splicing in Plant Development - Kornblihtt, Alberto Rodolfo (2014)
In this issue of Developmental Cell, Bardou et al. (2014) elucidate how long, highly structured noncoding RNAs control alternative splicing regulators that specifically mediate the action of the hormone auxin in the promotion of lateral root growth in Arabidopsis.